Kinetic properties of mouse pancreatic lipase-related protein-2 suggest the mouse may not model human fat digestion - Xiao, Xunjun (The American Society for Biochemistry and Molecular Biology, 2011)
Genetically engineered mice have been employed to understand the role of lipases in dietary fat digestion with the expectation that the results can be extrapolated to humans. However, little is known about the properties of mouse pancreatic triglyceride lipase (mPTL) and pancreatic lipase-related protein-2 (mPLRP2). In this study, both lipases were expressed in Pichia Pastoris GS115, purified to near homogeneity, and their properties were characterized. Mouse PTL displayed the kinetics typical of PTL from other species. Like mPTL, mPLRP2 exhibited strong activity against various triglycerides. In contrast to mPTL, mPLRP2 was not inhibited by increasing bile salt concentration. Colipase stimulated mPLRP2 activity 2- to 4-fold. Additionally, mPTL absolutely required colipase for absorption to a lipid interface, whereas mPLRP2 absorbed fully without colipase. mPLRP2 had full activity in the presence of BSA, whereas BSA completely inhibited mPTL unless colipase was present. All of these properties of mPLRP2 differ from the properties of human PLRP2 (hPLRP2). Furthermore, mPLRP2 appears capable of compensating for mPTL deficiency. These findings suggest that the molecular mechanisms of dietary fat digestion may be different in humans and mice. Thus, extrapolation of dietary fat digestion in mice to humans should be done with care.